التداولية؛ مفاهيمها وجذورها الفلسفية واللسانية - عبد العزيز, مصباحي (جامعة الوادي - University of Eloued, 2021)
ملخص: يختلف النقاد المحدثون في تحديد مفهوم التداولية، فمنهم من يرى أنها جزء من علم العلامات أو السيميائية، ومنهم من يجعل منها دراسةً لمستويات استعمال الخطاب اللغوي. وهي تنطوي على ثلاثة مستويات: ذاتي، موضوعي، ومستوى مشترك بينهما؛ لذلك وجب الحرص على التفريق بين المصطلحات المتراكمة في كتب اللسانيات؛ وذلك مرده في الأساس لكثرة المقابلات التي قُدِّمَتْ للمصطلح الإنجليزي: «Pragmatics ». ومن هنا تأتي هذه الورقة البحثية لتبحث الأسباب التاريخية وغير التاريخية التي مهّدت لنشأة اللسانيات التداولية، وتعرض كذلك لمفهوم هذا المصطلح عند مختلف علماء الاتجاهات اللسانية؛ بدءًا من نظرية المنطق والدلالة، وانتهاءً إلى المفهوم التداولي الحديث. Abstract: Modern critics differ in defining the concept of Pragmatics; Some argue that it is a part of the semiotics, whereas others consider it as a study of the levels of the use of linguistic discourse. three levels are certainly involved in semiotics: A subjective level, an objective level, and a common level between them. Therefore, care should be taken to differentiate between the terminology accumulated in the books of linguistics relating to this fertile area of the linguistic lesson. This is mainly attributed to the large number of the corresponding translations of the English term: “Pragmatics. Hence. this research paper examines the historical and non-historical reasons that paved the way for the emergence of Pragmatic Linguistics. It also presents the definition of this term among different linguists from the Theory of Logic and semantics to the modern concept of Pragmatics.
Keywords: تداولية ; فلسفة ; دلالة ; جذور ; خطاب